"Plough" by A.M. Pires Cabral: a proximity landscape - Alves, Isabel Maria Fernandes (2012)
Based on Plough, published in 2009, this reflection aims to consider the poetry of A.M. Pires Cabral through the lens of ecocriticism. In this sense, the text begins by noting the various landscapes that are part of the poet’s life and art and how they, transformed into language, become the poet himself. Subsequently, some of poems are read according to the critical frame of ecocriticism and the conviction that language can have a strong grasp on how one reads and interprets the land and the landscape. Sensitive to the connections between man and the physical space he inhabits, ecocriticism reinforces an important perspective on Cabral’s poetry: the recognition that human culture affects the physical world and is affected by it.